2018
DOI: 10.1002/jcb.28228
|View full text |Cite
|
Sign up to set email alerts
|

Identification of hub genes to regulate breast cancer metastasis to brain by bioinformatics analyses

Abstract: Breast cancer with metastasis especially brain metastasis represents a significant cause of morbidity and mortality in patients. In this study, we aimed to investigate the hub genes and potential molecular mechanism in brain metastasis breast cancer. Expression profiles of the genes were extracted from the Gene Expression Omnibus (GEO) database. GO and KEGG pathway enrichment analyses were conducted at Database for Annotation, Visualization, and Integrated Discovery. Protein-protein interaction (PPI) network w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 32 publications
1
48
0
Order By: Relevance
“…Similarly, it has been reported that high SKA3 expression promotes lung cancer cell proliferation and predicts patient outcomes. Through bioinformatics analysis, Tang et al found that SKA3 is associated with elevated susceptibility to breast cancer brain metastasis and negatively correlates with breast cancer survival (75). Our data further validate the correlation between high SKA3 expression and advanced clinical features of G3/G4.…”
Section: Discussionsupporting
confidence: 81%
“…Similarly, it has been reported that high SKA3 expression promotes lung cancer cell proliferation and predicts patient outcomes. Through bioinformatics analysis, Tang et al found that SKA3 is associated with elevated susceptibility to breast cancer brain metastasis and negatively correlates with breast cancer survival (75). Our data further validate the correlation between high SKA3 expression and advanced clinical features of G3/G4.…”
Section: Discussionsupporting
confidence: 81%
“…The application of bioinformatics methods has identified multiple genes including protein coding genes and non-coding genes associated with cancer progression. 14,15 Numerous miRNAs have been shown to be abnormally expressed in CRC. For instance, expression of miR-483-3p was reported to be downregulated in oxaliplatin-resistant CRC cell lines; it regulates cell migration and apoptosis by targeting FAM171B.…”
Section: Discussionmentioning
confidence: 99%
“…Knockdown of SKA3 expression activates the spindle assembly checkpoint with loss of sister chromatid cohesion, leading to mitotic arrest during metaphase 12 , 13 . SKA3 is implicated in the development and progress of lung adenocarcinoma, prostate cancer, cervical cancer, and breast cancer 14 17 . Here, we show that SKA3 is also highly expressed in LSCC, and higher levels of SKA3 are closely associated with poorer clinicopathological characteristics.…”
Section: Introductionmentioning
confidence: 99%